Damage optimisation for air bending - Guhr, Fabian; Barthold, Franz-Joseph (Technische Universität Dortmund, 2021)
Load and shape optimisation are applied to the process of air bending to optimise the damage state in the formed component. The enhanced process of elastomer bending is optimised, which yields a reduced damage state due to the superimposed radial stresses in the critical area of the forming process. The optimisation presented here is twofold. First, the elastomer is replaced by nodal loads to generate optimised loads for a reduced damage state. Second, the elastomer itself is optimised via shape optimisation by adjusting the layer for two kinds of elastomer of varying stiffness. The optimisation is accomplished with the commercial FEM software Abaqus as the solver for the mechanical problem and Matlab is used for optimisation.
Proceedings in applied mathematics & mechanics;Vol. 20. 2021, Issue 1, e202000074
Keywords: 690